Modeling Larval Connectivity of Coral Reef Organisms in the Kenya-Tanzania Region - Mayorga-Adame, C. Gabriela; Batchelder, Harold P.; Spitz, Yvette. H. (Frontiers in Marine Science, 2017)
Most coral reef organisms have a bipartite life-cycle; they are site attached to reefs as adults but have pelagic larval stages that allow them to disperse to other reefs. Connectivity among coral reef patches is critical to the survival of local populations of reef organisms, and requires movement across gaps that are not suitable habitat for recruitment. Knowledge of population connectivity among individual reef habitats within a broader geographic region of coral reefs has been identified as key to developing efficient spatial management strategies to protect marine ecosystems. The study of larval connectivity of marine organisms is a complex multidisciplinary challenge that is difficult to address by direct observation alone. An approach that couples ocean circulation models with individual based models (IBMs) of larvae with different degrees of life-history complexity has been previously used to assess connectivity patterns in several coral reef regions [e.g., the Great Barrier Reef (GBR) and the Caribbean]. We applied the IBM particle tracking approach to the Kenya-Tanzania region, which exhibits strong seasonality in the alongshore currents due to the influence of the monsoon. A 3-dimensional (3D) ocean circulation model with 2 km horizontal resolution was coupled to IBMs that track virtual larvae released from each of 661 reef habitats, associated with 15 distinct regions. Given that reefs provide homes to numerous species, each with distinctive, and in aggregate very diverse life-histories, several life-history scenarios were modeled to examine the variety of dispersal and connectivity patterns possible. We characterize virtual larvae of Acropora corals and Acanthurus surgeonfish, two coral reef inhabitants with greatly differing pelagic life-histories, to examine the effects of short (<12 days) and long (>50 days) pelagic larval durations (PLD), differences in swimming abilities (implemented as reef perception distances), and active depth keeping in reef connectivity. Acropora virtual larvae were modeled as 3D passive particles with a precompetency period of 4 days, a total PLD of 12 days and a perception distance of 10 m. Acanthurus virtual larvae were characterized by 50 days precompetency period, a total PLD of 72 days and a perception distance of 4 km. Acanthurus virtual larvae were modeled in two ways—as 3D passive particles and including an idealized ontogenetic vertical migration behavior. A range of distances within which larvae were able to perceive reefs and directionally swim to settle on them during the competency period were evaluated. The influence of interannual environmental variations was assessed for 2 years (2000, 2005) of contrasting physics. The spatial scale of connectivity is much smaller for the short PLD coral, with successful connections restricted to a 1° radius ( 100 km) around source reefs. In contrast, long distance connections from the southern to the northernmost reefs ( 950 km) are common for virtual Acanthurids. Successful settlement for virtual Acropora larvae was <0.3%, and within region settlement (local retention) was 0.38%, substantially greater than inter-region settlement (ca. 0.2%). Settlement of Acanthurus virtual larvae was >20% overall, with cross-region recruitment much increased compared to the coral larvae. Approximately 8% of Acropora larvae that successfully settled, recruited to their source reef (self-recruitment), an important proportion compared to only 1–2% self-recruitment for Acanthurus. These rates and dispersal distances are similar to previous modeling studies of similar species in other coral reef regions and agree well with the few observational studies within the Kenya-Tanzania region.